Burying the bumblebee once and for all: Does big government hurt growth less in high-trust countries? - Andreas Bergh; Christian Bjørnskov (Research Institute of Industrial Economics (IFN), 2016)
High levels of social trust has been linked to both public sector size and long term economic growth, thereby helping to explain how some countries are able to combine high taxes and relatively high levels of economic growth. This paper examines if social trust as a background factor also insulates countries against negative effects of public sector size on growth, as government size and growth are found to be negatively associated in several recent studies. We note that the effect is theoretically ambiguous. In panel data from 66 countries across 40 years, we find little robust evidence of insulating effects. Instead we find robust evidence that high trust aggravates the crowding out effects of public sector size on private investments.
Keywords: H10; O11; P16; Z10; 330; trust; economic growth; government consumption